Elite capture, political voice and exclusion from aid: an experimental study - Ben D'Exelle; Arno Riedl (Institute for the Study of Labor (IZA), 2008)
We experimentally study the influence of local information conditions on elite capture and social exclusion in community-based development schemes with heterogeneous groups. Not only information on the distribution of aid resources through community-based schemes, but also information on who makes use of an available punishment mechanism through majority voting may be important. The main results are the following. First, many rich community representatives try to satisfy a political majority who would then abstain from using the punishment mechanism, and exclude those community members whose approval is then not required. The frequency of this exclusion strategy is highest with private information on the distribution and public voting. Second, when voting is public, responders are more reluctant to make use of the punishment mechanism, and representatives who follow the exclusion strategy are more inclined to exclude the poorest responder. Third, punishment is largely ineffective as it induces rich representatives to capture all economic resources. Fourth, if a poor agent takes the representative's role, punishment rates drop, efficiency increases, and final distributions become more equal.
urn:nbn:de:101:1-2008091734
Keywords: D72; 330; Distribution of aid; inequality; social exclusion; laboratory experiment; Entwicklungshilfe; Verteilungspolitik; Bürgerbeteiligung; Public Choice; Soziale Isolation; Soziale Ungleichheit; Interessenpolitik; Test